2017
DOI: 10.1007/s10461-017-2017-x
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the Menu of HIV Prevention Options: A Qualitative Study of Experiences with Long-Acting Injectable Cabotegravir as PrEP in the Context of a Phase II Trial in the United States

Abstract: Adherence challenges with oral pre-exposure prophylaxis have stimulated interest in alternate modes of administration including long-acting injections. We conducted 30 in-depth interviews with 26 male trial participants and 4 clinical providers in a Phase IIa study (ÉCLAIR) evaluating the use of long-acting cabotegravir (CAB-LA) injections in New York and San Francisco. Interviews exploring attitudes and experiences with CAB-LA were audiotaped, transcribed, and analyzed using thematic content analysis. Despite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 44 publications
1
48
0
Order By: Relevance
“…It is noteworthy that participants' attitudes towards product attributes, including receiving two injectionsone in each buttock every two-months, was a stronger predictor of future interest in use than were their experiences with pain and other side effects. These findings are similar to acceptability data recently presented from a phase 2 trial of Cabotegravir LA (CAB LA) injectable (HPTN 077) [30] and a qualitative sub-study of ECLAIR, a phase 2 trial of CAB LA in MSM, which found overall high levels of acceptability, despite frequent but variable experiences of pain [31]. As additional long-acting PrEP modalities like implants and antibodies move through clinical trial research [32], there is an opportunity to further assess how participants understand and experience product features and the relative trade-offs they would consider in choosing and using a PrEP product.…”
Section: Discussionsupporting
confidence: 87%
“…It is noteworthy that participants' attitudes towards product attributes, including receiving two injectionsone in each buttock every two-months, was a stronger predictor of future interest in use than were their experiences with pain and other side effects. These findings are similar to acceptability data recently presented from a phase 2 trial of Cabotegravir LA (CAB LA) injectable (HPTN 077) [30] and a qualitative sub-study of ECLAIR, a phase 2 trial of CAB LA in MSM, which found overall high levels of acceptability, despite frequent but variable experiences of pain [31]. As additional long-acting PrEP modalities like implants and antibodies move through clinical trial research [32], there is an opportunity to further assess how participants understand and experience product features and the relative trade-offs they would consider in choosing and using a PrEP product.…”
Section: Discussionsupporting
confidence: 87%
“…We identified that a fear of needles may impede LAI use in some, but these fears were assuaged through having a health provider administer the injection, thinking of needles as a blood draw that they are familiar with, or remembering that the injection will provide protection from HIV. Educational programing that addresses these reported concerns with injectable PrEP use and that incorporates these case scenarios (i.e., injectable options for birth control and diabetes treatment) is crucial for increasing PrEP uptake by community members during early phases of the PrEP implementation process with these new products [32, 52]. Furthermore, injectable PrEP could be administered by a pharmacist or other health provider within pharmacy-based clinics, an emerging delivery model in the US, to address some of these reported barriers [53, 54].…”
Section: Discussionmentioning
confidence: 99%
“…The qualitative interviews demonstrated the importance of the convenience of an LA injectable as providing "peace of mind," an overall sense that the participants were interested in continuing treatment even with minor injection soreness, noting a perceived advantage of not "having to remember to adhere to a daily oral regimen." 18 All participants reported being satisfied with cabotegravir LA injection for PrEP, would recommend it as an alternative treatment, and would be interested in continuing when the option becomes commercially available. Disadvantages identified included the needles being relatively long and the location of the injection site was uncomfortable.…”
Section: Discussionmentioning
confidence: 99%
“…In a separate substudy of participants in ECLAIR, qualitative interviews were conducted with 26 volunteers at two sites (New York, n ¼ 15; San Francisco, n ¼ 11) to determine participants' experience with cabotegravir LA. 18 Oral consent was obtained from the Johns Hopkins Bloomberg School of Public Health Institutional Review Board onsite.…”
Section: Pro Assessmentsmentioning
confidence: 99%